2015
DOI: 10.3390/en81212404
|View full text |Cite
|
Sign up to set email alerts
|

Radiometric Characterization, Solar and Thermal Radiation in a Greenhouse as Affected by Shading Configuration in an Arid Climate

Abstract: Abstract:Shading the greenhouses is necessary in summer to reduce the solar radiation load. This however generates a considerable amount of thermal radiation heat load that needs to be removed via cooling systems. This study aimed to evaluate the effect of different shading configurations on the solar and thermal radiation in a greenhouse. Nets at four different locations were employed to shade the roof and side-walls of a polycarbonate, mechanically ventilated greenhouse. The spectral radiative properties of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 29 publications
(41 reference statements)
0
20
0
Order By: Relevance
“…This has led to the rapid expansion of the use of greenhouses for crop protection. The critical challenge facing greenhouse operation under these conditions is the unacceptable increases of the inside greenhouse air temperature, which requires appropriate cooling methods to provide a favorable environment for crop growth [1,2]. Preventing solar heat load from entering the greenhouse is the most appropriate method for cooling greenhouses in arid regions [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This has led to the rapid expansion of the use of greenhouses for crop protection. The critical challenge facing greenhouse operation under these conditions is the unacceptable increases of the inside greenhouse air temperature, which requires appropriate cooling methods to provide a favorable environment for crop growth [1,2]. Preventing solar heat load from entering the greenhouse is the most appropriate method for cooling greenhouses in arid regions [3].…”
Section: Introductionmentioning
confidence: 99%
“…Preventing solar heat load from entering the greenhouse is the most appropriate method for cooling greenhouses in arid regions [3]. Through this method, solar radiation can be reduced before entering the greenhouse by cutting-off (via absorption or reflection) a portion of the incident radiation on the greenhouse cover [1][2][3]. This can be accomplished by deploying fixed or movable shading nets below or above the roof of the greenhouse [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Active blind-type shading systems have been investigated widely for building applications [54]. However, such systems have been investigated only rarely for greenhouse applications, although shading control is extremely important in greenhouse cultivations [12]. In the present manuscript, a novel PV blind system specific for greenhouse applications is presented.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, installing PV arrays partially on a greenhouse roof might be preferred if the PV panels are intended as shading materials. Shading is a fundamentally important practice for greenhouse cultivation in high-insolation regions, such as Spain [11] or Saudi Arabia [12]. Previous studies conducted in Japan [13] and in the Mediterranean region [14,15] demonstrated that an adequate level of shading mitigates excessive temperature rises in greenhouses in summer, improving crop growth and quality [16,17].…”
mentioning
confidence: 99%